Potential of Nanoparticles as Permeation Enhancers and Targeted Delivery Options for Skin: Advantages and Disadvantages - Ghasemiyeh P; Mohammadi-Samani S (Dove Medical Press, 2020)
Parisa Ghasemiyeh,1,2 Soliman Mohammadi-Samani2,3 1Department of Clinical Pharmacy, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 2Department of Pharmaceutics, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 3Center for Nanotechnology in Drug Delivery, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Soliman Mohammadi-Samani Tel +987132426070Fax +987132424126Email smsamani@sums.ac.irAbstract: The topical route of administration has many advantages for the treatment of various skin disorders as well as cosmeceutical purposes. This route bypasses hepatic first-pass effect and systemic availability of many pharmaceuticals is limited to skin organelles such as hair follicles and so could avoid unwanted adverse reactions and increase the localized therapeutic effect. Despite such attributed advantages of the topical route, the most important challenge is skin barrier characteristics that should be overcome to obtain dermal or trans-dermal drug delivery. Different approaches have been recruited to overcome this barrier. In this review, different types of nanoparticles for skin permeation enhancement and targeted delivery to skin organelles are discussed. The potential mechanisms of each nanocarrier in permeation enhancement and dermal delivery are considered and finally, the most important advantages and disadvantages of each group are summarized.Keywords: nanoparticles, skin permeation, skin organelles, topical drug delivery, advantages, disadvantages